2021
DOI: 10.5114/ain.2021.109545
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alcohol use and associated factors among students of medical sciences in central Iran

Abstract: No ghostwriting and guest authorship declared./Nie występują zjawiska ghostwriting i guest authorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Several studies have recently indicated in Iran that smoking has increased among the young generation, especially Iranian students (16,17). High alcohol consumption has also been reported among Iranian students in other studies (18,19). Furthermore, the rate of obesity, overweight, and consumption of high-salt and high-fat foods is critically growing among most Iranian students (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently indicated in Iran that smoking has increased among the young generation, especially Iranian students (16,17). High alcohol consumption has also been reported among Iranian students in other studies (18,19). Furthermore, the rate of obesity, overweight, and consumption of high-salt and high-fat foods is critically growing among most Iranian students (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%